Dynamic changes of muscle insulin sensitivity after metabolic surgery - Sofiya Gancheva (Nature Portfolio, 2019)
Surgical weight-loss interventions improve insulin sensitivity via incompletely understood mechanisms. Here the authors assess skeletal muscle epigenetic changes in individuals with obesity following metabolic surgery and compare them with data from individuals without obesity.